2020
DOI: 10.1002/hbm.24926
|View full text |Cite
|
Sign up to set email alerts
|

Cortical laminar resting‐state signal fluctuations scale with the hypercapnic blood oxygenation level‐dependent response

Abstract: Calibrated functional magnetic resonance imaging can remove unwanted sources of signal variability in the blood oxygenation level-dependent (BOLD) response. This is achieved by scaling, using information from a perfusion-sensitive scan during a purely vascular challenge, typically induced by a gas manipulation or a breath-hold task. In this work, we seek for a validation of the use of the resting-state fluctuation amplitude (RSFA) as a scaling factor to remove vascular contributions from the BOLD response. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 80 publications
9
50
0
Order By: Relevance
“…The somatosensory CBV changes in response to whisker stimulation peak in the range of 5%-10% (compared to the baseline CBV). Such amplitudes are consistent with previously reported ΔCBV estimates in the pre-clinical domain (Hillman et al 2007;Kennerley et al 2005;2012a;Lee et al 2001;Tian et al 2010), whereas they are about 5-10 times smaller than previously reported VASO signal changes in humans (Beckett et al 2020;Chai et al 2019;Finn et al 2019;Guidi et al 2017;Huber et al 2018;Kurban et al 2020;Persichetti et al 2020;Yang and Yu 2019;Yu et al 2019).…”
Section: Concomitant Ois and Vasosupporting
confidence: 93%
See 2 more Smart Citations
“…The somatosensory CBV changes in response to whisker stimulation peak in the range of 5%-10% (compared to the baseline CBV). Such amplitudes are consistent with previously reported ΔCBV estimates in the pre-clinical domain (Hillman et al 2007;Kennerley et al 2005;2012a;Lee et al 2001;Tian et al 2010), whereas they are about 5-10 times smaller than previously reported VASO signal changes in humans (Beckett et al 2020;Chai et al 2019;Finn et al 2019;Guidi et al 2017;Huber et al 2018;Kurban et al 2020;Persichetti et al 2020;Yang and Yu 2019;Yu et al 2019).…”
Section: Concomitant Ois and Vasosupporting
confidence: 93%
“…The VASO CBV profile, however, also exhibits a similarly elevated CBV response in the superficial layers. This is consistent with previous layer-fMRI VASO studies (Beckett et al 2020;Chai et al 2019;Donahue et al 2017;Finn et al 2019;Guidi et al 2017;Huber et al 2014a;2017;Kurban et al 2020;Persichetti et al 2020;Yang and Yu 2019;Yu et al 2019) and might appear in conflict with the large body of preclinical studies. Note that the superficial activity in VASO profiles is located within the cortex and is approx 0.8 mm deeper than the GE-BOLD peak response above the cortical surface.…”
Section: Vaso Vs Mion Derived Cbv and Associated Cortical Profilingsupporting
confidence: 91%
See 1 more Smart Citation
“…To examine if the laminar neuronal specificity of the signal can be recovered from the data, we used a normalisation approach. Normalisation of laminar profiles have been proposed previously in the context of resting-state fMRI [157,158] using BOLD fluctuation power to probe connectivity across areas and with induced hypercapnia [158]. These normalisation approaches are motivated by the fact that the baseline parameters, such as venous CBV (V0), are assumed to be multiplicative for BOLD sensitivity and conforms to the single-vascular-compartment BOLD signal models (as in Davis et al [159], Buxton et al [160]).…”
Section: Laminar Profile Normalisationmentioning
confidence: 99%
“…Thus, calibrating the BOLD signal to another condition or time point (or baseline fluctuations [157,158]) effectively removes the bias stemming from baseline physiological and physical parameters. For the case that neuronal profiles of two stimuli or time-points are just scaled versions of each other (i.e.…”
Section: 3)mentioning
confidence: 99%